Meeting report of the 5th Heidelberg Myeloma Workshop: current status and developments in diagnosis and therapy of multiple myeloma - Merz, Maximilian; Hillengaß, Jens; Goldschmidt, Hartmut (Journal of cancer research and clinical oncology, 2016)
PURPOSE: The 5th Heidelberg Myeloma Workshop was held on April 24 and 25, 2015, in the lecture hall of the department of internal medicine of the University Hospital of Heidelberg, Germany. - METHODS AND RESULTS: Main topics of the meeting were (1) new insights into biology of plasma cell diseases, (2) familial risk in multiple myeloma (MM), (3) diagnosis and prognostic factors in MM and early plasma cell diseases, (4) frontline therapy in transplant-eligible and (5) transplant-ineligible patients as well as (6) treatment of relapsed disease. - CONCLUSION: Better understanding of disease biology led to tremendous changes in the treatment of multiple myeloma in recent years and were reported during the meeting.
Published online: 12 June 2015
Gesehen am 04.05.2020